(untitled) (AYUSHDHARA, 2021)
Today in the era of information and technology the whole scenario has been changed. Women have a multidimensional attitude and enjoy special place in the society by reaching all kinds of heights by their spectacular physical and mental performance in almost all possible fields. Problems of different age group of women are still present and the most suffering age group is forty plus due to change in reproductive life by cessation of menstruation causing untoward physical and mental agonies called menopause. Every woman faces various physiological and psychological changes during this change as part of hormonal de arrangement. The presence of regular menstruation indicates the starting of reproductive life of women and menopause indicates the declining fertility rate of female. Rajonivritti word is made up of two different words viz., ‘Rajah and Nivritti Rajah denoted as Aartava (menstrual blood) Nivritti as Uprama (cessation). In Ayurveda this phenomenon taken in different way not as a serious health problem. As Sushruta mentioned that menopause deals with Jarapakvya avastha of the body. Sometimes such disturbances attain the stage of disease or syndrome called Menopausal Syndromes accompanied by various vasomotor, psychological, genital, locomoter and G.I.T related symptoms.